The Oxford handbook of the archaeology of death and burial - Tarlow, Sarah; Nilsson Stutz, Liv (Oxford handbooks, 2013)
This handbook reviews the state of mortuary archaeology and its practice with 44 chapters focusing on the history of the discipline and its current scientific techniques and methods. Written by leading scholars in the field, it derives its examples and case studies from a wide range of time periods and geographical areas.